Governance Implementation in a Public-Private Partnership Project: Stakeholders’ Perspective - Devi, Dias Shinta; Adib, Noval; Rahmanti, Virginia Nur (Riviera Publishing, 2025)
This study aims to evaluate the governance implementation of the MHPP Bintang Bano Project from the perspective of the involved stakeholders. This research uses a qualitative case study approach and stakeholder theory as an analytical framework. Data collection was carried out through interviews with eight informants and documentation. The data were analyzed using the Interactive Model. The evaluation focuses on six dimensions of governance: policy, regulation, institutional, stakeholder, transparency, and accountability. The findings indicate that the project has applied good governance principles across these six dimensions, however several challenges remain, such as the lack of regulatory integration across sectors, uncertainty in the electricity tariff setting, and the lengthy procurement process for the implementing private entity.